The Enhanced Musical Rhythmic Perception in Second Language Learners - Roncaglia-Denissen, M. Paula; Roor, Drikus A.; Chen, Ao; Sadakata, Makiko (Frontiers in Human Neuroscience, 2016)
Previous research suggests that mastering languages with distinct rather than similar rhythmic properties enhances musical rhythmic perception. This study investigates whether learning a second language (L2) enhances the perception of musical rhythmic variation in general, regardless of first and second languages’ rhythmic properties. Additionally, we investigated whether this perceptual enhancement could be alternatively explained by exposure to musical rhythmic complexity, such as the use of compound meter in Turkish music. Finally, it investigates if an enhancement of musical rhythmic perception could be observed among L2 learners whose first language relies heavily on pitch information, as is the case with tonal languages. Therefore, we tested Turkish, Dutch and Mandarin L2 learners of English and Turkish monolinguals on their ability to perceive musical rhythmic variation. Participants’ phonological and working memory capacities, melodic aptitude, years of formal musical training and daily exposure to music were assessed to account for cultural and individual differences which could impact their rhythmic ability. Our results suggest that mastering a second language rather than exposure to musical rhythmic complexity could explain individuals’ enhanced perception of musical rhythmic variation. An even stronger enhancement of musical rhythmic perception was observed for L2 learners whose first and second languages differ regarding their rhythmic properties, as enhanced performance of Mandarin and Turkish in comparison with Dutch L2 learners of English seem to suggest. Our findings provide further support for a cognitive transfer between the language and music domain, which may find its grounds on a common evolutionary basis.